Singing Training According to Notation at the Immanuel Kotaraja Evangelical Camp Congregation - Ferre, Godfried San; Layan, Santy; Gobai, Mika; Patasik, Serli (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
overcome the congregation's limitations in reading musical notation, which often hinders the harmony and beauty of music in worship. This training aims to improve the ability of congregations, worship leaders and musicians to understand and apply musical notation correctly. The methods used include demonstrations and questions and answers, which help the congregation be more active in absorbing the theory and practice of ecclesiastical music. As a result, this training has had a significant positive impact on the quality of music services. The congregation is not only more synchronized in singing praise songs, but also better able to appreciate the spiritual meaning of each song sung. In addition, the ability to read notation opens up opportunities for the congregation to explore more creative and varied arrangements, enriching the worship atmosphere musically and spiritually. In conclusion, this training contributed to improving the quality of church music, strengthening congregational togetherness, and deepening their spiritual experience in worship. This initiative also supports higher education institutions' efforts to implement Tri Dharma, especially in the field of community service.